The Wonderful World of Queer Cinephilia - Ghosh, Shohini (BioScope: South Asian Screen Studies, 2010)
The silence around queerness is decisively broken. Much has happened in the last two decades. Today, there are queer groups, writers, activists, academics, filmmakers, and an increasing number of spaces where friendship, solidarity, and political engagement can be nurtured. Queer activism has been responsible for bringing a legal challenge to Section 377 (IPC) that criminalizes “sexual acts against the order of nature”.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Créateur.rice LGBTQ+; _Nettoyé

From Rage to Resignation: Reading Tina Mabry’s Mississippi Damned as a Post–Civil Rights Response to Nina Simone’s “Mississippi Goddam” - Moore, Marlon Rachquel (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Much has been written about Nina Simone’s song “Mississippi Goddam” because it lyrically achieves the political consciousness of the embattled community whose experiences and energy it intends to speak to, through, and for. With its curse words, impatient tone, and energetic rhythm, it could never be mistaken for the traditional, Christian-inflected civil rights dirge. “Alabama’s got me so upset,” the chorus complains. “Tennessee made me lose my rest, and,” as if its atrocities need not be spelled out, “every body knows about Mississippi, goddam!” The song was banned from radio airplay but still became part of the civil rights sound
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; _Nettoyé